(untitled) (The Review of Diabetic Studies, 2025)
Background: Treatment adherence is a recurring problem in healthcare delivery, and rates of non-adherence of 20-50% have been found in various chronic diseases. Multidisciplinary interventions such as social services, nursing, and pharmacy interventions have been demonstrated to overcome multiple barriers to adherence effectively. Objective: the effectiveness of multidisciplinary collaborative interventions by social services, nursing, and pharmacy in enhancing treatment adherence in chronic patients. Methods: Prospective 12-month questionnaire survey was performed among 450 chronic disease patients. Patients were randomly divided into intervention (n=225) and control (n=225) groups. Intervention group underwent coordinated pharmacy care, nursing, and social services. Morisky Medication Adherence Scale-8 (MMAS-8) and self-reported questionnaires were used to assess treatment adherence at baseline, 6 months, and 12 months. Results: There was better adherence score in the intervention group (5.2 ± 1.8) at baseline to 12 months (7.1 ± 1.2) than in controls (5.3 ± 1.7 to 5.8 ± 1.9; p<0.001). The secondary outcomes like quality of life, medication knowledge, and healthcare use were significantly improved in the intervention group. Conclusion: Nursing, social services, and pharmacy teams’ multi-disciplinary interventions synergistically work together to enhance patient outcomes and treatment adherence. The multi-disciplinary intervention proves to be effective in overcoming a variety of adherence barriers simultaneously and must be included as a standard part of providing care.